Pengaruh Penyuluhan Kesehatan Tentang Hipertensi Kehamilan Terhadap Pengetahuan Ibu Dalam Memelihara Tekanan Darah di Desa Padang Pulau Kabupaten Asahan - donna budiyanthy (Universitas Prima Indonesia, 2019)
ABSTRACT Mother's knowledge about the problem of hypertension in pregnancy is still relatively low. Lack of knowledge about hypertension in pregnancy reflects a lack of knowledge about the risks associated with their fetus and how to avoid them. Based on preliminary studies carried out in the Padang pulau village Kabupaten Asahan regency that has been conducted by researchers note that in 2013 there were 48 pregnant women whose blood pressure> 140 mmHg. In the January to April 2018 there were 35 pregnant women. This study aims to determine the relationship of health education on hypertension in pregnancy with the mother's knowledge in maintaining blood pressure in Padang pulau village Kabupaten Asahan regency This type of research was analytic observational with cross sectional design. The population in this research was all pregnant women and a sample of 35 people, engineering samples of the total sampling, methods of collecting data by interviewing indirectly by used a questionnaire, data analysis using Chi-Square test. Based on the results of the analysis showed that pvalue (0.004) <α (= 0.05), which shall mean the hypothesis was accepted that there was a relationship of health education on hypertension in pregnancy with the mother's knowledge in maintaining blood pressure. For it was expected that health workers in order to carry out health education as one of health promotion actions in order to prevent hypertension in pregnancy and can improve maternal and child health.